Serum insulin-like growth factor (IGF)-I and IGF-binding protein-3 concentrations and prostate cancer risk: Results from the European prospective investigation into cancer and nutrition - Allen, N; Key, T; Appleby, P; Travis, R; Roddam, A; Rinaldi, S; Egevad, L; Rohrmann, S; Linseisen, J; Pischon, T; Boeing, H; Johnsen, N; et al. (2007)
Background: Some studies suggest that elevated serum insulin-like growth factor (IGF)-I concentrations are associated with an increased risk of prostate cancer and, in particular, with an increased risk of advanced-stage prostate cancer. Methods: We analyzed the association between prediagnostic serum concentrations of IGF-I and IGF-binding protein-3 (IGFBP-3) and prostate cancer risk in a case-control study nested in the European Prospective Investigation into Cancer and Nutrition. This study includes 630 incident prostate cancer cases and 630 matched control subjects. Odds ratios and their 95% confidence intervals (95% CI) were calculated for prostate cancer risk associated with increasing IGF-I and IGFBP-3 concentrations using conditional logistic regression. Results: The risk of total prostate cancer in the highest versus the lowest third of serum peptide concentration was 1.35 (95% CI, 0.99-1.82; P trend = 0.08) for IGF-I, 1.39 (95% CI, 1.02-1.89; Ptrend = 0.12) for the IGF-I residuals after adjusting for IGFBP-3, 1.22 (95% CI, 0.92-1.64; Ptrend = 0.38) for IGFBP-3, and 1.01 (95% CI, 0.74-1.37; Ptrend = 0.75) for the IGFBP-3 residuals after adjusting for IGF-I. There was no significant difference in the association of peptide hormones and prostate cancer by stage of disease, although the association of serum IGF-I concentration with risk was slightly stronger for advanced-stage disease; the odds ratio for the highest versus the lowest third was 1.65 (95% CI, 0.88-3.08; Ptrend = 0.21) for IGF-I and 1.76 (95% CI, 0.92-3.40; P trend = 0.11) for IGF-I adjusted for IGFBP-3. Conclusions: In this large nested case-control study, serum IGF-I concentration is not strongly associated with prostate cancer risk, although the results are compatible with a small increase in risk, particularly for advanced-stage disease; no association for IGFBP-3 was observed. Copyright © 2007 American Association for Cancer Research.